2019
DOI: 10.1016/j.jclepro.2019.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the attitude-behaviour gap paradox for sustainable food consumption: Insight from the UK apple market

Abstract: The remarkable progress made by the sustainable food industry as compared to the persistent small market share it holds, presents attitude-behaviour gap paradox which existing research is yet to address. The paper attempts to resolve this conundrum by addressing two key research objectives: Firstly, we draw on Campbell's paradigm to develop a sustainable product purchase behaviour model by conceptualising and measuring behavioural difficulties in terms of behavioural inhibitors/promoters, which includes Past P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 104 publications
6
68
0
Order By: Relevance
“…Tanner and Kast [22] (2003) emphasized the importance of variables such as attitudes, behavioral intention, and individual characteristics including demographics and psychographics to uncover the potential sustainable consumer. A recent study on purchase intentions toward sustainable foods also showed that psychosocial variables like attitudes, beliefs, and subjective norms, more than demographics, independently predict purchase intention for sustainable products [23] (Yamoah and Acquaye, 2019). Despite several studies reporting on barriers and consumer profiles, there is a gap in thorough understanding of consumer decision-making toward sustainable consumption, especially in terms of apparel.…”
Section: Sustainable Apparel Consumption In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Tanner and Kast [22] (2003) emphasized the importance of variables such as attitudes, behavioral intention, and individual characteristics including demographics and psychographics to uncover the potential sustainable consumer. A recent study on purchase intentions toward sustainable foods also showed that psychosocial variables like attitudes, beliefs, and subjective norms, more than demographics, independently predict purchase intention for sustainable products [23] (Yamoah and Acquaye, 2019). Despite several studies reporting on barriers and consumer profiles, there is a gap in thorough understanding of consumer decision-making toward sustainable consumption, especially in terms of apparel.…”
Section: Sustainable Apparel Consumption In Chinamentioning
confidence: 99%
“…Both researchers and practitioners have struggled with the lack of commensuration between industry growth and market share and sought out a solution via attitude-behavior research [23] (Yamoah and Acquaye, 2019). This study paid attention to the attitude-behavior gap model to investigate determinants of sustainable consumption in China.…”
Section: Attitude and Behavior Gap In Sustainable Consumer Decision Mmentioning
confidence: 99%
“…Examples of non-food products are sportswear [72], fashion products [44,73], clothing [39], fashion, beauty, and home décor [74], laundry detergent, and sanitizing wipes [75]. Researchers studied ecological, green, and sustainable products, such as ecological food products [76], eco-friendly products [77], grocery products with an eco-label [49], eco-labelled food [78], eco-fashion [79], green food and groceries [80], green fashion products [52], green products [81], sustainable seafood [38], apples from the sustainable food categories [40], sustainable household and personal care products [58], environmentally sustainable apparel [82], sustainability certified food products [41], and local food products [50].…”
Section: Results: Retail Contextmentioning
confidence: 99%
“…The contextual factors related to the geographic areas are diverse, reflecting the European, American, and Asian markets. Most articles focus on European markets, especially the UK [38][39][40][41]46,[53][54][55]60,70,[83][84][85] and Sweden [41][42][43]46,47,54,59,72,74,76,77,86]. Other European countries considered by the reviewed articles include Austria [41], Belgium [45,73,78], Denmark [41,54], France [38,49,54], Finland [87], Germany [38,54,60,73], Italy [38,50], Netherlands [51,73,88], Norway [38], Poland [38], Spain [38], and Switzerland [69,…”
Section: Results: Retail Contextmentioning
confidence: 99%
“…According to Vega-Zamora et al [56], the choice of one product over another depends on the consumers' perceived benefits. Accordingly, the preference for natural food does not always translate into purchasing these foods [8] because it depends on other factors, such as the willingness to pay premium prices [6,8,[57][58][59], the product label information [15,59,60], and the variety and availability of natural food for purchasing [57]. However, there is a consensus among the literature that "trust" could be a predictor of consumer intentionality and behavior [8,56,61,62].…”
Section: Methodsmentioning
confidence: 99%